Radiological image processing advantages applied to human age estimation based on dental parameters. (June 2019) - Mazzilli, Luiz Eugenio Nigro; Melani, Rodolfo Francisco Haltenhoff; Lascala, Cesar Angelo; Mariano, Gabriel Gonçalves; Sakaguti, Nelson M.; Cameriere, Roberto
Highlights: Fiji_ImageJ integral image filter resource can improve both accuracy and reproducibility over a reference method for adults age estimation. Considered Cameriere's (2008) pulp/tooth ratio methodology, the experimental protocol expressed not only a better adherence to the linear regression equation (an increase of 10% in the determination coefficient), but also an one-year reduction considered both the Standard Error of the mean (SE) and the mean of the residuals (RM). The more visible and sharper contours under filtered examinations seem to have contributed to the intra-rater and to the inter-rater concordance score improvement; ranging respectively from 8% to 9% higher in the experimental protocol.